Implementasi Perencanaan Manajemen Marketing Solution Services Perusahaan Pedagang Besar Farmasi & Alat Kesehatan Di PT. Jagat Pharma Abadi - Andri Subyakto; Tantri Yanuar Rahmat Syah; Edi Hamdi; Dihin Septyanto (Syntax Corporation Indonesia, 2024)
The health budget over the past five years has experienced a significant increase in 2020, a budget of 119.9 trillion (T) increased to 124.4 trillion (T) in 2021, 134.8 trillion (T) in 2022, and 172.5 trillion (T) in 2023. In 2024, this budget is projected at 186.4 trillion (T), or 5.6% of the state budget. This budget increased by 8.1% or 13.9 trillion compared to 2023. Of the total state budget for the Ministry of Health of 186.4 trillion, it is projected that the distribution will flow to Rp2,537,921,988,000.00 for Vertical Hospitals (RS) and Rp2,021,730,483,000.00 for Regional General Hospitals. The purpose of this research is to see how much potential this business has for the Jakarta and Banten areas. This method uses a working framework for this business plan, which consists of marketing objectives, marketing strategy, mix management, sales volume and company revenue plan. The results of this study are goals and objectives in the pende, long-term and long-term which are the benchmarks for the study in achieving the targets in each division. The conclusion of this study explains how the company achieves the predetermined targets by using methods in marketing planning by using the maximum number of sales and budget. This research explains that the method or way of achieving the company's target needs continuity between each division.